Child adoption as an oppressive child protection practice: The voices of adopted adolescents in Zimbabwe - Muzingili, Taruvinga; Gozho, Charles Simbarashe; Mabeza, Tinos Toindepi; Chidyausiku, Weston; Muzondo, Edward (Social Work/Maatskaplike Werk, 2025)
Adoption is globally recognised as a child protection strategy, offering children without parental care a stable family environment. However, this study explores how adoption processes in Zimbabwe can perpetuate oppressive dynamics, particularly by marginalising the voices of adopted adolescents. Using anti-oppressive practice (AOP) as the theoretical framework, the study employed a social constructionist, interpretative phenomenological analysis (IPA) approach to examine the lived experiences of 19 adolescents aged 14–17 who had contested their adoptions. Data were collected through semi-structured interviews, analysed thematically using IPA principles and supported by MAXQDA software. Findings revealed that adolescents felt disempowered and excluded from the adoption process, leading to emotional distress, cultural disconnection and identity crises. They reported secrecy, lack of transparency and inadequate support from social workers, coupled with mixed feelings of gratitude and resentment toward adoptive parents. With the currently closed adoption model prioritising children from 5 years and below, the study underscores that current adoption practices in Zimbabwe often marginalise children’s voices and sever cultural ties, perpetuating oppressive dynamics. This calls for reforms emphasising transparency, inclusivity and cultural preservation. Adoption processes should empower children, respect their rights and foster open communication to promote holistic wellbeing and identity continuity.